y+(y+1)+7=56

Simple and best practice solution for y+(y+1)+7=56 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y+(y+1)+7=56 equation:


Simplifying
y + (y + 1) + 7 = 56

Reorder the terms:
y + (1 + y) + 7 = 56

Remove parenthesis around (1 + y)
y + 1 + y + 7 = 56

Reorder the terms:
1 + 7 + y + y = 56

Combine like terms: 1 + 7 = 8
8 + y + y = 56

Combine like terms: y + y = 2y
8 + 2y = 56

Solving
8 + 2y = 56

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 2y = 56 + -8

Combine like terms: 8 + -8 = 0
0 + 2y = 56 + -8
2y = 56 + -8

Combine like terms: 56 + -8 = 48
2y = 48

Divide each side by '2'.
y = 24

Simplifying
y = 24

See similar equations:

| 4l=n-2 | | 5x+5=5x-6 | | 98x+10y=9435 | | 8/2x=16 | | 22-18=2(x-3) | | a+b+(b+13)=180 | | 14=3x/2 | | 3xz=9 | | 3+2n=7b | | 16b-25=0 | | 25x-6+15x-4=20x+10 | | 7lnx= | | y=6+9x | | 19+x/3-3=17 | | 7b=2n+3 | | -2x+70=13x-5 | | 5/21-2/15= | | 5/×=20/12 | | -5y+11=y+17 | | 5x/12=8x-12 | | -6(x-11)=11-27+4 | | 2/5x-1/4x=12 | | 70=a/6-10 | | 4y-5x=11 | | x+(x*0.2)=90 | | h=42 | | T=2m+2u | | 4z-0.8=4 | | 1=2(x+6)-3x | | 5n-13=-2n+1 | | 4x=24+2(3x-6) | | 38=t/4+8 |

Equations solver categories